(untitled) (Revista Nacional de Odontología, 2016)
Introduction: this article determines the frequency, variability, sexual dimorphism, corres-pondence and bilateral symmetry of nine coronal dental morphological traits (cdmt) in the secon-dary temporary molars and primary permanent molars of three ethnic groups in the Choco region. Materials and method: transversal quantitative descriptive study that characterizes the dental mor-phology of the primary temporary molars (55, 65, 75, 85) and primary permanent molars (16, 26, 36, 46) in 83 study models: 24 indigenous Emberá people (13 women and 11 men), 27 afro descendants (16 women and 11 men) and 32 Caucasoid mestizos (18 women and 14 men). A p < 0,05 was con-sidered statistically significant. Results: the superior molars presented moderate rates of the cusp of Carabelli represented in pits and fissure expressions, low frequency of metaconule and absence of reduction of the hypocone; and in the inferior molars, almost absolute expression of the p point of the protosthilide, mild frequency of deflective wrinkle, configuration of cusp patterns y5 and y6 and relative frequencies of cusp 6 and 7. The cmdt do not present sexual dimorphism (except the cusp 6 of Afro-descendants and Caucasian mestizo); they have low correspondence and count with bilateral symmetry. Conclusion: the three ethnic groups are clustered in the same conglomerate near popula-tions belonging to the Caucasoid Dental Complex (which gathers the Occidental Dental Complex, the Sub-Saharan Dental Complex and the African Saharan Dental Complex) associated with the ethno-historical influence of African slaves, be by progeny or by miscegenation